PENERAPAN ALGORITHMA POHON UNTUK OPERASI PENGOLAHAN DAN PENYIMPANAN DATA DALAM TEKNIK PEMROGRAMAN (KAJIAN ALGORITHMA POHON PADA TEKNIK PEMROGRAMAN) - Fitri Latifah (Jurnal Techno Nusa Mandiri, 2016)
The implementation of algorithms in a programming technique is very important, the algorithm is expressive of one of the teaching methods, algorithms can also be used to explain how a formal system of a number of axioms And rules. For some cases, the algorithm should be carefully formulated to how each step should be systematically organized case by case this is because the algorithm is a set of steps - the appropriate steps, the sequence of computing. In the computer structure, scientific terms of data is a way to prepare and organize the storage of data on the storage medium that can be used effectively. Tree (tree) is a connected graph that contains no circuits. Tree (tree) is a data structure that is not linear and represented with hierarchical relationships between elements.